PENGARUH KUALITAS SARANA DAN PRASARANA PENDIDIKAN TERHADAP BRAND IMAGE MADRASAH DINIYYAH TAKMILIYYAH AL JAMHURIYAH KARAWANG - Afifah, Najwa; Astuti Darmiyanti; Chairil Fajar Hadiansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Educational facilities and infrastructure are essential components of learning services and visible evidence through which parents assess the quality and professionalism of an educational institution. This study examines the effect of the quality of educational facilities and infrastructure on the brand image of Madrasah Diniyyah Takmiliyyah (MDT) Al Jamhuriyah Karawang. A quantitative associative-causal design was used. The population consisted of 136 parents, and 58 respondents were selected through proportionate stratified random sampling using a 10% Slovin error level. Data were collected through a four-point Likert questionnaire, observation, and documentation. The analysis included descriptive statistics, Pearson correlation, simple linear regression, t-test, and coefficient of determination. The results show that the quality of facilities and infrastructure was rated good with a Weighted Mean Score of 3.253, while brand image was also rated good with a score of 3.227. The Pearson correlation was 0.760, indicating a strong positive relationship. Regression analysis produced Y = 7.819 + 0.749X, with t = 8.738 and p < 0.001. The coefficient of determination was 0.577, meaning that facilities and infrastructure explained 57.7% of the variation in brand image. These findings indicate that improving the availability, feasibility, comfort, cleanliness, safety, and Islamic suitability of facilities can strengthen the perceived image of a nonformal Islamic educational institution.